[13C]‐galactose breath test in a patient with galactokinase deficiency and spastic diparesis. Issue 1 (3rd February 2021) - Ficicioglu, Can; Demirbas, Didem; Derks, Britt; Pai, G. Shashidhar; Timson, David J.; Rubio‐Gozalbo, Maria Estela; Berry, Gerard T.
Abstract: Galactokinase deficiency is an inborn error of carbohydrate metabolism due to a block in the formation of galactose‐1‐phosphate from galactose. Although the association of galactokinase deficiency with formation of cataracts is well established, the extent of the clinical phenotype is still under investigation. We describe a 6‐year‐old female who was diagnosed with galactokinase deficiency due to cataract formation when she was 10 months of age and initially started on galactose‐restricted diet at that time for 5 months. She developed gait abnormality at 4 years of age. Breath tests via measurement of 13 C isotope in exhaled carbon dioxide following 13 C‐labeled galactose administration at carbon‐1 and carbon‐2 positions revealed oxidation rates within the normal range. The results in this patient strikingly contrast with the results of another patient with GALK1 deficiency that underwent breath testing with [1‐ 14 C]‐galactose and [2‐ 14 C]‐galactose. Extension of in vivo breath tests to other galactokinase patients is needed to better understand the pathophysiology of this disease.